1995
DOI: 10.1093/oxfordjournals.humrep.a136098
|View full text |Cite
|
Sign up to set email alerts
|

Infertility: The desire for multiple births in couples with infertility problems contradicts present practice patterns

Abstract: Paradoxically, the attitude of infertility patients towards multiple births has never been investigated. We therefore generated a survey by questionnaire, which was sent to 3800 consecutive unselected couples with infertility problems: 582 responses were received (15% response rate) and analysed. The percentage distribution of the responses to 21 questions, addressing attitudes towards and knowledge about the risk of multiple gestations, was the main outcome. Worry about multiple births was expressed, independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
2
14

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(86 citation statements)
references
References 0 publications
1
69
2
14
Order By: Relevance
“…Although some earlier studies have reported finding a more favourable attitude towards a multiple birth was associated with increased age in female IVF patients [29,38] this study did not find a significant correlation. However, in accord with previous studies [29][30][31]38] parity and previous cycles of IVF were associated with a more favourable attitude towards twins.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Although some earlier studies have reported finding a more favourable attitude towards a multiple birth was associated with increased age in female IVF patients [29,38] this study did not find a significant correlation. However, in accord with previous studies [29][30][31]38] parity and previous cycles of IVF were associated with a more favourable attitude towards twins.…”
Section: Discussioncontrasting
confidence: 93%
“…However, in accord with previous studies [29][30][31]38] parity and previous cycles of IVF were associated with a more favourable attitude towards twins. This may reflect the desire for an instant family.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, medical contraindications aside, the older the patient, the more likely it should be viewed as a very favorable outcome. Sound additional arguments in favor of twin pregnancies can also be made based on patient rights to self determination and patient preferences [16,19].…”
Section: Discussionmentioning
confidence: 99%
“…They, however, do not raise the possibility that this observation, alone, may suggest potential biases based on maternal age in embryo numbers transferred, as older women are more desirous of twin pregnancies [16]. They also leave unmentioned that 96.3 % of twin-mothers and a full 99.0 % of mothers of consecutive singletons were under age 40, though ages of singleton mothers at each of their two pregnancies remain undefined.…”
Section: A General Critique Of the Swedish Studymentioning
confidence: 90%
See 1 more Smart Citation